2021
DOI: 10.1155/2021/4032285
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Timing of Simethicone Supplement for Bowel Preparation: A Prospective Randomized Controlled Trial

Abstract: Background and Aims. Simethicone (SIM), as an antifoaming agent, has been shown to improve bowel preparation during colonoscopy. However, the optimal timing of SIM addition remained undetermined. We aimed to investigate the optimal timing of SIM addition to polyethylene glycol (PEG) to improve bowel preparation. Methods. Eligible patients were randomly assigned to two groups: the SIM evening group (SIM addition to PEG in the evening of the day prior to colonoscopy) and the SIM morning group (SIM addition to PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
(28 reference statements)
1
8
0
Order By: Relevance
“…A study showed that taking simethicone significantly reduced bubbles, [ 4 ] while a study was conducted to determine the most effective dose of simethicone [ 14 ] and another study was conducted to determine the most effective timing of taking simethicone. [ 9 , 10 ] Also, there was a study that posed mixing simethicone with 2 L of PEG-ascorbic acid solution for both bowel cleansing and eliminating bubbles was better. [ 5 ] There is no clearly established protocol to date, but when the results of previous studies are combined, it can be thought that taking 200 mg of simethicone on the day before the examination is most effective.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study showed that taking simethicone significantly reduced bubbles, [ 4 ] while a study was conducted to determine the most effective dose of simethicone [ 14 ] and another study was conducted to determine the most effective timing of taking simethicone. [ 9 , 10 ] Also, there was a study that posed mixing simethicone with 2 L of PEG-ascorbic acid solution for both bowel cleansing and eliminating bubbles was better. [ 5 ] There is no clearly established protocol to date, but when the results of previous studies are combined, it can be thought that taking 200 mg of simethicone on the day before the examination is most effective.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that taking simethicone significantly reduced bubbles, [4] while a study was conducted to determine the most effective dose of simethicone [14] and another study was conducted to determine the most effective timing of taking simethicone. [9,10] Also, there was a study that posed mixing simethicone with 2 L .796 †BB = the day before the examination and before bowel cleansing. ‡BA = the day before the examination and after bowel cleansing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it resulted in lower bubble scale scores and a lower intraprocedural use of simethicone [4]. Furthermore, the optimal timing of oral simethicone addition remains undetermined [9,10]. In summary, previous studies were mostly from Eastern countries, used low-volume PEG-based regimens or non-PEG-based agents, used simethicone in suspension, have shown conflicting results and only one study assessed colonoscopy results in a CRC screening setting.…”
Section: Introductionmentioning
confidence: 99%